Association between the intact foreskin and inferior standards of male genital hygiene behaviour: a cross-sectional study. - O'Farrell, N; Quigley, M; Fox, P (2005)
This study was undertaken to determine whether non-circumcised men have inferior standards of genital hygiene behaviour, as measured by reported washing of the whole penis, compared with circumcised men. Male attenders at a sexually transmitted infections (STI) clinic at Ealing Hospital, London had routine STI tests and examinations performed and were asked about the frequency and thoroughness of genital washing. One hundred and fifty non-circumcised and 75 circumcised men were enrolled. Not always washing the whole penis, including retracting the foreskin in non-circumcised men every time they washed (defined as inferior genital hygiene behaviour) was more common in non-circumcised (26%) than circumcised men (4%) (crude odds ratio = 8.43, 95% confidence interval: 2.51-28.3, P<0.001) and those with balanitis (42% and 5%, P=0.036). Circumcised men were more likely than non-circumcised men to wash the genital area more than once a day (37% and 19%, P=0.011). Studies investigating the relationship between male circumcision status and other outcomes, for example HIV infection, should include assessment of genital hygiene.